Description of the Burnout Pandemic on Nurses in the Isolation Room at RSUD Wangaya Denpasar - Sukmayanti, Luh Putu; Kiki Rizki Fista Andriana; Ni Gusti Ayu Putu Triyani; Ni Made Nopita Wati (Basic and Applied Nursing Research Journal, 2021)
During this pandemic, health workers, especially nurses, are at the forefront of dealing with the Covid-19 outbreak. Nurses will experience stress, this is because the workload that occurs on nurses is very large, so nurses tend to experience pandemic burnout. The purpose of this study was to determine the description of the pandemic burnout on nurses in the Isolation Room of Wangaya Hospital Denpasar based on 3 dimensions of burnout. Data collection tool using Maslach Burnout Inventory questionnaire. This research method is descriptive quantitative by using a survey. The sample in this study was selected with a total sampling technique of 39 respondents. The results of this study are most of the respondents experienced pandemic burnout in the low category as many as 32 people (82.1%). Dimension emotional exhaustion most of the respondents answered "always" as many as 7 people (17.9%), the dimension depersonalization most of the respondents answered "always" as many as 13 people (33.3%) and the dimension of dimished personal accomplishment most of the respondents answered "always" as many as 1 person (2.6%). This pandemic has occurred for more than a year, nurses are getting used to their work and are used to using level 3 PPE. It is recommended for nurses to be in isolation rooms, attend webinars or seminars on handling Covid-19 patients, psychological webinars, yoga, and other spiritual improvement activities that can reduce nurse burnout.